Different languages, similar encoding efficiency: Comparable information rates across the human communicative niche - Coupé, Christophe; Oh, Yoon; Dediu, Dan; Pellegrino, François (Science Advances, 2019)
Language is universal, but it has few indisputably universal characteristics, with cross-linguistic variation being the norm. For example, languages differ greatly in the number of syllables they allow, resulting in large variation in the Shannon information per syllable. Nevertheless, all natural languages allow their speakers to efficiently encode and transmit information. We show here, using quantitative methods on a large cross-linguistic corpus of 17 languages, that the coupling between language-level (information per syllable) and speaker-level (speech rate) properties results in languages encoding similar information rates (~39 bits/s) despite wide differences in each property individually: Languages are more similar in information rates than in Shannon information or speech rate. These findings highlight the intimate feedback loops between languages’ structural properties and their speakers’ neurocognition and biology under communicative pressures. Thus, language is the product of a multiscale communicative niche construction process at the intersection of biology, environment, and culture.
Keywords: Construction process; Encoding efficiency; Information rates; Language levels; Natural languages; Neurocognition; Quantitative method; Shannon information; Communication; Heterogeneous-Nuclear Ribonucleoproteins; Humans; Language; Linguistics; Speech